2021
DOI: 10.3389/fmed.2021.614380
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Validation of an Automated Search Strategy to Retrospectively Identify Acute Respiratory Distress Patients Per Berlin Definition

Abstract: Purpose: Acute respiratory distress syndrome (ARDS) is common in critically ill patients and linked with serious consequences. A manual chart review for ARDS diagnosis could be laborious and time-consuming. We developed an automated search strategy to retrospectively identify ARDS patients using the Berlin definition to allow for timely and accurate ARDS detection.Methods: The automated search strategy was created through sequential steps, with keywords applied to an institutional electronic medical records (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…8,23,24 Despite being high, the incidence of ARDS in hospitalized patients is likely underestimated in most studies, as physicians do not always document this diagnosis in the medical records. 29 After ARDS, the most common complications were altered mental status and renal failure, with one-fth of the hospitalized elderly patients developing acute kidney injury. Other cohort studies assessing hospitalized elderly patients have reported acute kidney injury, which is likely related to tubular injury caused by local and systemic in ammation and immune systems, aggravated by hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…8,23,24 Despite being high, the incidence of ARDS in hospitalized patients is likely underestimated in most studies, as physicians do not always document this diagnosis in the medical records. 29 After ARDS, the most common complications were altered mental status and renal failure, with one-fth of the hospitalized elderly patients developing acute kidney injury. Other cohort studies assessing hospitalized elderly patients have reported acute kidney injury, which is likely related to tubular injury caused by local and systemic in ammation and immune systems, aggravated by hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study considers any adult patient placed on mechanical ventilation, which requires evaluating all Berlin Definition components. Finally, Song and Li developed a fully rules-based tool that automates the entire Berlin Definition, both achieving identical high performance 13,14 . However, their models were constructed within a single hospital, which may not be reproducible across different health systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a ML algorithm to risk stratify patients for ARDS using structured clinical data derived from the EHR was shown to have good discriminative performance 12 . Regarding automating the entire ARDS diagnostic algorithm, two studies 13,14 have recently reported implementation of keyword search (i.e. rule-based approach) in the EHR with validation conducted for 100 intensive care unit (ICU) admissions from a single time period and from a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital billing codes are insufficient to create such a dataset due to clinical under-recognition [ 14 ]. Automated methods to filter patient encounters using constraints on clinical features from the Electronic Medical Record (EMR) like PaO 2 /FiO 2 ratio, or positive end-expiratory pressure (PEEP) defined by the Berlin criteria are being approached [ 17 ], but are limited by non-standard documentation across EMR [ 18 ], and the heterogeneity of clinical manifestations of ARDS [ 19 ]. Thus, clinician adjudication of retrospective data is needed, which involves meticulous inspection of patient history using the EMR.…”
Section: Introductionmentioning
confidence: 99%